Anisotropic and Shape-Selective Nanomaterials Structure-Property Relationships - Hunyadi Murph, Simona E.; Larsen, George K.; Coopersmith, Kaitlin J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book reviews recent advances in the synthesis, characterization, and physico-chemical properties of anisotropic nanomaterials. It highlights various emerging applications of nanomaterials, including sensing and imaging, (bio)medical applications, environmental protection, plasmonics, catalysis, and energy. It provides an excellent and comprehensive overview of the effect that morphology and nanometric dimension has on the physico-chemical properties of various materials and how this leads to novel applications.
Part I: Introduction and Fundamentals -- An Introduction to Nanotechnology -- Nanoscale Materials: Fundamentals and Emergent Properties -- Synthetic Strategies for Anisotropic and Shape-Selective Nanomaterials -- Characterization of Anisotropic and Shape-Selective Nanomaterials: Methods and Challenges -- Part 2: Effect of the morphology and the nanometric dimension of materials on their physico- chemical properties -- Anisotropic Metallic and Metallic Oxide Nanostructures - Correlation between their shape and properties -- Putting Nanoparticles to Work: Self-propelled Inorganic Micro- and Nanomotors -- Prospects for rational control of nanocrystal shape through successive ionic layer adsorption and reaction (SILAR) and related approaches -- Plasmon Drag Effect. Theory and Experiment -- Dimensional Variations in Nanohybrids: Property Alterations, Applications, and Considerations for Toxicological Implications -- Assemblies and Superstructures of Inorganic Colloidal Nanocrystals -- Nanostructured Catalysts for the Electrochemical Reduction of CO2 -- Strategies for the Synthesis of Anisotropic Catalytic Nanoparticles -- Biomedical Applications of Anisotropic Gold Nanoparticles -- Application of Gold Nanorods in Cardiovascular Science -- Architectured Nanomembranes -- Summary and Final Thoughts.
Keywords: Nanochemistry; Nanotechnology; Lasers; Inorganic chemistry; Nanochemistry; Nanotechnology; Laser; Inorganic Chemistry